Optimization of the Separation and Validation Method for Ginsenoside Re and Ginsenoside Rg1 Compounds in Panax Ginseng Powder Extract Using the HPLC Method: A Systematic Literature Review - Marzella Dea Rossardy; Azminah (Jurnal Penelitian Pendidikan IPA, 2024)
The analytical methods used to analyze ginsenoside compounds include TLC, HPTLC, HPLC, UPLC, GC and MS. The HPLC method is the most widely used analytical technique with various combinations of UV detection or with ELSD. The HPLC method is a method of separating and purifying chemical compounds or medicinal compounds. To study new information from optimization for the separation of ginsenoside Re and ginsenoside Rg1 compounds, then validate the analytical method to show that the method provides accurate results in accordance with the requirements. The data and information used in this review article come from national and international journals. The data and information search method was carried out using the literature research method. keywords: "Optimization of Separation and Method Validation of Ginsenoside Compounds using the HPLC method" with a journal publication period 2019-2023. Of the 35 research articles found, only 9 journals met the inclusion and exclusion criteria. Studies on ginsenoside compounds Re and Rg1 in ginseng plants are still not well separated. So it’s still necessary to optimize the analytical method using the HPLC method and then validate the analytical method to show that the method provides accurate results in accordance with the requirements.